Microhabitat de Tolypothrix distorta Kütz. ex Bornet & Flahault (Microchaetaceae, Cyanophyta) em dois riachos da região Centro-Sul do Estado do Paraná, Brasil - Krupek, Rogério Antonio; Branco, Ciro Cesar Zanini [UNESP]; Peres, Cleto Kaveski (Instituto de Botânica, 2013)
This study aimed to evaluate some microhabitat characteristics of two populations of Tolypothrix distorta in streams from midsouthern region of Paraná State on a seasonal period. Each population was monthly investigated for the abundance of T. distorta and environmental variables such as depth, current velocity, irradiance, richness, and substrate diversity (H') using the quadrat technique for each sample unit (n = 7-10). For each segment the following physical and chemical water variables were also measured: temperature, oxygen saturation, specific conductance, pH, and turbidity. The seasonal period of higher abundance (percent cover) occurred during the months corresponding to summer/fall for both populations. The analyses also showed that populations had lower niche width and wide variation under the environmental conditions, characterizing the species as a generalist in the use of resources. Faster water flow and larger substrates favored the development of T. distorta, which may be related to the species morphological characteristics, thallus type that consists of tangled filaments formed by tuft and covered with thick gelatinous coats.
Microhabitat of Tolypothrix distorta Kütz. ex Bornet & Flahault (Microchaetaceae, Cyanophyta) in two streams from midsouthern region of Paraná State, Brazil
Keywords: autoecology; macroalgae; Tolypothrix distorta; seasonal variation